Antibodies to N-homocysteinylated albumin as a marker for earlyonset coronary artery disease in men - Undas, Anetta; Jankowski, Milosz; Twardowska, Magdalena; Padjas, Agnieszka; Jakubowski, Hieronim; Szczeklik, Andrzej (Thrombosis and Haemostasis, 2005)
N-homocysteinylated (Nε-Hcy) proteins and corresponding antibodies have recently been discovered in humans and animals. Increased autoimmune response to Nε -Hcy-proteins has been reported in stroke patients. The aim of the present study was to investigate whether antibodies against N-homocysteinylated albumin are associated with coronary artery disease (CAD).We studied 88 male patients aged 50 years or under with angiographically documented CAD and 100 age-matched apparently healthy men as controls. Serum levels of IgG antibodies against Nε-Hcy-albumin were determined using an enzymelinked immunosorbent assay. Seropositivity to anti-Nε -Hcy-albumin antibodies was 5-fold more frequent in CAD patients than in controls (52.3 % vs 10.0 %; p<0.0001). Plasma Hcy levels in CAD patients were also significantly higher in the former than in the latter group (medians, 13.0 μ M vs 12.1 μ M; p=0.026). Importantly, 41.2% of subjects with plasma total Hcy >14.5 mM were seropositive compared with 25.5 % of normohomocysteinemic individuals (p=0.048).There was a weak correlation between anti-Nε-Hcy-albumin antibodies and Hcy levels (r=0.16; p=0.03). By multivariate logistic regression analysis, seropositivity to anti-Nε-Hcy-albumin antibodies was an independent predictor of early CAD (OR, 14.82; 95% CI, 4.47 to 49.19; p=0.00002). Interestingly, anti-Nε-Hcy-albumin antibodies were associated with C-reactive protein levels (r=0.24; p=0.002). Seropositivity to anti-Nε-Hcy-albumin antibodies showed no association with the MTHFR C677T polymorphism. Our results suggest that seropositivity to antibodies against Nε-homocysteinylated albumin is associated with early-onset CAD. An autoimmune response to Nε-Hcy-albumin may represent a novel mechanism involved in the early development of CAD.
Keywords: Antibodies; homocysteine; coronary artery disease